Disponibilidade hídrica para outorga de captação: critérios anual e mensal para definição de vazões mínimas de referência - Amorim Júnior, Joãozito Cabral (2014)
Brazilian water resources control agencies generally adopt in water resources use grant analysis processes constant maximum water use flow valuesthroughout the year, corresponding to percentages of minimum reference flows, Q90, Q95 or Q7,10, calculated from long period daily flow records. This adoption of constant flows does not consider there al existence of season alityin water availability in water sheds. This work analyses and compare maximum use flow grant values varying throughout the year, with adoption of Q90 and Q95 reference flows calculated for each month of the year, with those calculated from constant reference flow rates for all months of the year, according to the criteria currently used in Brazil. There were considered water discharges information for gauging stations located in all Brazilian and Espírito Santo state geographical regions. There was observed the occurrence of different seasonal characteristics for different gauging stations records, especially for those located in southern Brazil. It was concluded that the replacement of the annual criteria, currently adopted for water use grants request analysis, for the monthly criteria would result in large gains in water availability for users. Thus, the use of criteria based on monthly flows would largely increase the supply of demands by all owing greater water resources use in months of the year in which there are generally higher water availability. Analysis of positive and negative social, economic and environmental consequences of replacing annual criteria for monthly ones is suggested. It is recommended the adoption, if possible, of similar reference flow rates and grant analysis criteria in different Brazilian states since there is no hydrologic basis for the present differences.